Keputusan Penggunaan Go-ride Selama Covid-19 - Saeni, Asrini A.; Pasande, Grace Yunita; Rizaldi, Andi Risfan (Universitas Sulawesi Barat, 2023)
This was motivated by the existence of a pandemic situation which resulted in most of the economic activities being halted and had an impact on all sectors including daring transportation. Profit levels can be maintained if the company can design a marketing strategy and implement security as an important factor in choosing online transportation services. This study aims to see whether marketing and security strategies affect the decision to use Go-ride during Covid-19. This study uses a quantitative method with a total of 159 respondents with Go-ride user criteria, the analytical tool used is multiple linear regression analysis using SPSS version 21. The results of the study show that marketing has a positive and significant effect on usage decisions, security has a positive effect on usage decisions, marketing strategy and security simultaneously influence the decision to use